고등학교 프랑스어 수행평가 실태 연구 - 김정숙(Jungsug Kim) (Language Research, 2020)
This study aims to explore the current situation and specifics as well as teacher understanding of the performance assessment that exists at the center of the current curriculum assessment, which was revised in 2015. The results of a survey of 35 high school French teachers and 14 of the respondents' assessment plans are as follows. Firstly, although the application of the French-language performance assessment (measured in percentage) has increased, the assessment does not seem to function as an assessment of higher order thinking due to the students' limited French ability. Secondly, French teachers are positively aware of the performance assessment, and they attempt to optimize its proper function. In particular, assessments in the cultural areas are conducted for the aspects of creativity, logical thinking, and justice. Thirdly, the greatest difficulty teachers face in terms of implementing the performance assessment is securing objectivity and fairness; this is followed by teachers having to manage an increase in tasks such as grading. Lastly, the study demonstrates that the assessment of different performance areas by their respective teachers can be a significant issue given the potential for error in classifying areas and the lack of feasibility with respect to assessment standards. This seems to be an urgent issue for which a solution should be prioritized, especially in light of the fact that college admissions based on performance evaluations are set to be officially implemented.